2020
DOI: 10.3390/su12166591
|View full text |Cite
|
Sign up to set email alerts
|

Does Servant Leadership Moderate the Relationship between Job Stress and Physical Health?

Abstract: High school teachers experience high levels of job stress, which could lead to serious health problems. This study focused on Chinese high school teachers, as they have to manage negative stress and health issues. The research aimed to: (1) investigate the relationship between hindrance job stress, depersonalization, and physical health; (2) investigate if servant leadership, in fact moderates the relationship between hindrance job stress and depersonalization, as well as physical health. The study desisgn was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 47 publications
1
10
0
Order By: Relevance
“…This result of the investigation is consistent with the theory on the dynamic essence of dual occupational stress. On the one hand, as Dooley et al (2020) noted, dual occupational stress is not a static, but an accumulative and a qualitative change process, wherein challenge stress and hindrance stress alternate as the degree of pressure changes. Specifically, R&D team members, whose focus is on the strategy generation to overcome difficulties with the challenge attribute of occupational stress, proactively participate in constructive innovation process.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This result of the investigation is consistent with the theory on the dynamic essence of dual occupational stress. On the one hand, as Dooley et al (2020) noted, dual occupational stress is not a static, but an accumulative and a qualitative change process, wherein challenge stress and hindrance stress alternate as the degree of pressure changes. Specifically, R&D team members, whose focus is on the strategy generation to overcome difficulties with the challenge attribute of occupational stress, proactively participate in constructive innovation process.…”
Section: Discussionmentioning
confidence: 99%
“…As pointed out by LePine et al (2004) ; Edwards et al (2014) , and Dooley et al (2020) , dual occupational stress is considered in terms of two separate, theoretically deduced attributes: challenge occupational stress and hindrance occupational stress. This classification conforms to the classic research of LePine et al (2004) , who advocated that a comprehensive assessment of dual occupational stress should capture both conducive occupational stress (i.e., furthering one’s career) and inconducive occupational stress (i.e., hindering one’s current and future development).…”
Section: Theory Review and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…The highly significant correlation between servant leadership and resilience was in line with Rai and Prakash's (2016) study as servant leadership was positively correlated with absorptive capacity through perceived organizational support. Tang, Kwan, Zhang, and Zhu (2016) found that servant leadership facilitated work-family balance through emotional healing by reducing emotional exhaustion and enhancing personal learning while Dooley, Alizadeh, Qiu, and Wu (2020) highlighted that this acted as a buffer between hindrance stress and well-being. A Manager in Airport Operations passionately shared how he help achieve work-life balance: "Looking after work na meron syang pupuntahan, at hindi ko guguluhin ang off nya, at bibigyan ko sya ng sufficient rest, magiging happy yung tao.…”
Section: Spearman R P Value Decision Conclusionmentioning
confidence: 99%
“…Expectations on business leaders and organizations have changed dramatically in the last few years. Servant leadership with the focus on humility, and employee empowerment has become one of the most needed leadership styles for corporations (Dooley et al, 2020). While non-profit organizations struggling to solve societal crisis (Barhate et al, 2021), there is a growing belief that for-profit corporations need to contribute for the betterment of environment and society in addition to their own profits (Ashrafi, Adams, Walker, & Magnan, 2018;Chia, Kern, & Neville, 2020;Cheema, Afsar, & Javed, 2020).…”
Section: Introductionmentioning
confidence: 99%